Antimicrobial and mechanical acrylic resin properties with silver particles obtained from Fusarium oxysporum - Sato, Tabata Prado [UNESP]; Conjo, Celio Ilidio; Rossoni, Rodnei Dennis [UNESP]; Junqueira, Juliana Campos [UNESP]; De Melo, Renata Marques [UNESP]; Duran, Nelson; Borges, Alexandre Luiz Souto [UNESP] (Editora Cubo, 2018)
Objective: This study evaluated the effects of the incorporation of silver nanoparticles (AgNPs) obtained from Fusarium oxysporum on heat-activated acrylic resin (HAAR) and their influence on resin’s surface roughness, hardness, color alteration and antimicrobial capacity against Candida albicans. Material and Methods: For this, 50 discs of HAAR (2x5 mm) were produced and divided into three groups, Control: HAAR; Ag1: HAAR plus 0.539 mg of AgNPs; and Ag2: HAAR plus 1.1 mg of AgNPs. Knopp hardness (HK), surface roughness (Ra and Rz) and color alteration according to the CIE Lab were measured. Specimens were then evaluated in vitro with regard to C. albicans biofilm formation through formed colony count (CFU/mL). Scanning Electron Microscopy (SEM) and Atomic force microscopy (AFM) analyses were performed. Results: The addition of AgNPs of both concentrations changed Ra, Rz and HK significantly. There was statistically significant difference for L (p=0.00); a*(p=0.00) and b*(p=0.00) parameters. There were no differences between Ag1 and Ag2 biofilm formation, but the comparison of both with the control group presented a significant reduction (p=0.0091) on biofilm formation. SEM and AFM images showed no signs of NPs clustering. Conclusion: It can be concluded tha AgNPs incorporation in HAAR was effective in reducing C. albicans activity, with a slight change in color and hardness of the material, being effective therefore, in regions such as the dental prostheses palate, which have lesser aesthetic appeal.
Propriedades antimicrobiana e mecânica de resina acrílica com partículas de prata obtidas a partir de Fusarium oxysporum
Keywords: Acrylic resins; Antimicrobial agents; Silver